Respuesta :
Answer:
( 2,1) is the center of dilation and 4 is the scale factor
Step-by-step explanation:
A' = k( x-a) +a, k( y-b)+b where ( a,b) is the center of dilation and k is the scale factor
3,1 becomes 6,1
6,1 = k( 3-a) +a, k( 1-b)+b
6 = 3k -ka+a
1 = k -kb +b
4,1 becomes 10,1
10,1 = k( 4-a) +a, k( 1-b)+b
10 = 4k -ka+a
1 = k -kb +b
Using these two equations
6 = 3k -ka+a
10 = 4k -ka+a
Subtracting the top from the bottom
10 = 4k -ka+a
-6 = -3k +ka-a
------------------------
4 = k
Now solving for a
6 = 3k -ka+a
6 = 3(4) -4a+a
6 =12 -3a
Subtract 12
6-12 = -3a
-6 = -3a
Divide by -3
-6/-3 = -3a/-3
2 =a
Now finding b
1 = k -kb +b
1 = 4 - 4b+b
1 =4 -3b
Subtract 4
-3 = -3b
Divide by -3
1 = b
Answer:
Dilation factor: 4.
Center of dilation: (2, 1).
Step-by-step explanation:
The distance between the old vertices was 4 - 3 = 1. The distance between the new vertices is 10 - 6 = 4. 4 / 1 = 4. That means that the dilation factor is 4.
Now that we have a dilation factor, we can use the formulas x1 = d(x-a) +a and y1 = d( y-b)+b to solve for the center of dilation.
In this case, d = 4, x1 = 10, x = 4, y1 = 1, and y = 1.
10 = 4(4 – a) + a
10 = 16 – 4a + a
10 = 16 – 3a
-3a + 16 = 10
-3a = -6
a = 2
1 = 4(1 – b) + b
1 = 4 – 4b + b
1 = 4 – 3b
-3b + 4 = 1
-3b = -3
b = 1
And so, your center of dilation will be (2, 1).
Hope this helps!